The influence of family incivility on cyberbullying perpetration: A moderated mediation model - Gao, Jing; Liu, Fang; Xu, Jianjun; Wang, Jinyu; Mou, Jiaqi; Wang, Lingchao (Frontiers in Psychology, 2022)
Previous research has extended the stress literature by exploring the relationship between family incivility and cyberbullying perpetration, yet relatively less attention has been paid to underlying psychological mechanisms between that relationship among university students. According to the Frustration-Aggression Theory, this study examined the relationships of family incivility, cyberbullying perpetration, negative emotions and neuroticism among Chinese university students. Data were collected from 814 university students (females, N = 423; Mage = 19.96 years, SD = 3.09). The results examined the mechanism through which family incivility was significantly related to cyberbullying perpetration through the mediation of negative emotions, suggesting a strong link of stressful life events to online aggression. In addition, high levels of neuroticism moderated the relationship between family incivility and cyberbullying perpetration, as well as that between family incivility and negative emotions. The study revealed the chronic and potential impact of family incivility, underlined the interaction between stressful life events and online aggression, and put forward the intervention strategies of cyberbullying among university students.